ANALYSIS OF THE DYNAMICS AND TRENDS IN THE DEVELOPMENT OF MODERN INTERNATIONAL TOURIST MARKET - J. A. Pshenichnyh (Вестник университета)
Until recently, the tourism sector accounted for a significant share of the world's gross domestic product and provided about 10 % of world employment. In 2020, the global tourism industry faced a serious challenge – a crisis caused by the spread of a new type of virus (COVID-19 pandemic). International tourism has become one of the most affected by COVID-19 pandemic industries. The demand for tourism and hospitality services, which were one of the world's largest sources of foreign exchange earnings and employment in the era of pre-COVID-19, has significantly decreased. Although the future of tourism in an era of COVID-19 pandemic is very uncertain, a study of trends in the international tourism market in a crisis can be used to assess how the industry can recover and survive in the era of COVID-19 pandemic. Based on the statistical data of international organizations, the author studied indicators of international tourist flows, identified the main trends in the development of international tourism at the current stage, assessed the impact on the tourism sector of the COVID-19 pandemic and determined possibilities for its development in the context of the economic crisis, showed prospects for the development of the industry.